PENGARUH PANJANG LINI PRODUK DAN PROMOSI TERHADAP PENJUALAN PRODUK DI RSA AESTHETIC CLINIC - Novi, Ai novi munawaroh; Saad Noor (JEBS (Journal of Economic and Business Student), 2024)
The goal of this study is to examine and gain a general understanding of the impact of product line length and promotion on sales at Rsa Aesthetic Clinic. Quantitative descriptive statistics based on observation are the research approach utilized to gather the data for this study. The statistical tests used are inferential statistics using SPSS version 26 with Pearson product moment correlation test methods, determination coefficient tests, and T-test tests. The results of the Pearson product moment correlation test of product line length and promotion to product sales both show a significance of 0.000 < 0.05, meaning that there is a very strong correlation between product line length and promotion to product sales. The test results of the coefficient of determination of product line length of 0.774, or 77.4%, and promotion of 0.778, or 77.8%, had an effect on product sales, and the hypothesis was accepted. By using descriptive statistical analysis, determine the concentration and development trend up and down the length of product lines, product promotion, and sales.